ІГРОВІ ТА ТВОРЧІ ЗАВДАННЯ ЯК ЗАСІБ РОЗВИТКУ ПІЗНАВАЛЬНИХ ІНТЕРЕСІВ УЧНІВ ПРИ ВИВЧЕННІ ХІМІЇ (Педагогіка вищої та середньої школи, 2004)
The article is dedicated to the problem of the development of cognitive interests in chemistry lessons. The role o f creative and play tasks are shown as the means of the development of cognitive interests.